2001
DOI: 10.1176/appi.ajp.158.7.1105
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Prefrontal Cortex Dysfunction to Working Memory and Symptoms in Schizophrenia

Abstract: These results are consistent with the hypotheses that working memory dysfunction in patients with schizophrenia is caused by a disturbance of the dorsolateral prefrontal cortex and that this disturbance is selectively associated with cognitive disorganization. Further, the pattern of behavioral performance suggests that dorsolateral prefrontal cortex dysfunction does not reflect a deficit in the maintenance of stimulus representations per se but points to deficits in more associative components of working memo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

40
343
3
10

Year Published

2002
2002
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 566 publications
(396 citation statements)
references
References 52 publications
40
343
3
10
Order By: Relevance
“…This result gives support to the recent findings of Perlstein et al (2001Perlstein et al ( , 2003 who identified with separate tasks of WM and inhibitory control that participants with schizophrenia had particular difficulty under conditions of either high WM or prepotency demands. As the experimental demands increased and patient's performance began to suffer, a smaller increase in activation of the right DLPFC region was identified using fMRI, suggesting an insufficient ability to increase top-down control.…”
Section: Implications and Conclusionsupporting
confidence: 88%
“…This result gives support to the recent findings of Perlstein et al (2001Perlstein et al ( , 2003 who identified with separate tasks of WM and inhibitory control that participants with schizophrenia had particular difficulty under conditions of either high WM or prepotency demands. As the experimental demands increased and patient's performance began to suffer, a smaller increase in activation of the right DLPFC region was identified using fMRI, suggesting an insufficient ability to increase top-down control.…”
Section: Implications and Conclusionsupporting
confidence: 88%
“…There have been suggestions in the literature that, as NMDA antagonists induce psychotic symptoms and the NMDA receptor is involved in memory, the cognitive deficits observed in schizophrenia may be mediated by the NMDA receptor (eg Newcomer and Krystal, 2001). While cognitive impairment in schizophrenia still remains ill-defined, highly tentatively it appears that the profile of cognitive effects of ketamine appears somewhat similar to that observed in schizophrenia and organic psychosis (Perlstein et al, 2001), but differs in impairments to procedural learning and preserved executive functioning. Further research using techniques such as pharmacological functional magnetic resonance imaging may shed light on the similarity between neuroanatomical substrates of NMDA antagonist-induced cognitive impairments and those observed in schizophrenia.…”
Section: Discussionmentioning
confidence: 85%
“…Although there is considerable evidence that patients with schizophrenia fail to activate DLPFC to the degree seen in normal comparison subjects (termed hypofrontality) on a host of working memory or executive tasks including the Wisconsin Card-Sorting Task [Weinberger et al, 1986], the Tower of London [Andreasen et al, 1992], the n-back task [Carter et al, 1998], and verbal fluency [Yurgelun-Todd et al, 1996], more recent studies have stressed that DLPFC activation in patients is linked to performance deficits, with good performance associated with relatively greater DLPFC activity and marked behavioral deficits linked to relatively reduced DLPFC signal [Callicott et al, 2000;Perlstein et al, 2001;Ragland et al, 1998;Ramsey et al, 2002]. Manoach [2003] recently argued that task-related hypofrontality may be secondary to methodological issues or to between-group performance or motivational differences, and suggests that until the exact role of the prefrontal cortex in executive and working memory tasks is delineated, interpretation of reduced DLPFC activity in patients with schizophrenia is confounded.…”
Section: Introductionmentioning
confidence: 99%